Digital learning toy for children with dyslexia - Jose, Nazarina F.
Dyslexia is when a child's brain does not correctly recognize letters and/or words and as a result has difficulty in learning. This can be treated with special education services but for many parents these are unaffordable. Children may also find their learning sessions intimidating, boring or frustrating and would rather choose to play. And in this age of technology, it is common that children [prefer] digital gadgets over ordinary toys. Since playtime/toys and technology are both important for full development, the combination of these would be an effective and fun way to help dyslexic children. This toy has interactive, learning games designed specifically for dyslexia. These games have levels of difficulty to continually improve the child's reading ability. The toy is a convenient way to help children overcome their disability independently and enjoy too.